2011
DOI: 10.1063/1.3590771
|View full text |Cite
|
Sign up to set email alerts
|

Electronic tuning of magnetic permeability in Co2Z hexaferrite toward high frequency electromagnetic device miniaturization

Abstract: The magnetic and magnetostriction properties of Z-type cobalt-doped barium hexaferrite with perpendicular c-axis crystallographic texture are presented. The hexaferrite was utilized as a component in Co 2 Z/lead magnesium niobate-lead titanate multiferroic heterostructures whose tunability of permeability with electric field in terms of ferromagnetic resonance shift was supported by experiments and theoretical calculation. A permeability change of 16% was measured by an induced magnetic field of 38 Oe under th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…It was further revealed that the single crystalline Sr 2.48 Ba 0.52 Co 2 Fe 24 O 41 Z-type ferrite exhibits a magnetoelectric susceptibility of 3200 ps/m which was much higher than other room temperature single phase multiferroic materials, for example BiFeO 3 (55 ps/m)56. The findings of the room temperature magnetoelectric effects in Z-type hexaferrites will enable this material to be applied in the novel low-power magnetoelectronic devices78.…”
mentioning
confidence: 95%
“…It was further revealed that the single crystalline Sr 2.48 Ba 0.52 Co 2 Fe 24 O 41 Z-type ferrite exhibits a magnetoelectric susceptibility of 3200 ps/m which was much higher than other room temperature single phase multiferroic materials, for example BiFeO 3 (55 ps/m)56. The findings of the room temperature magnetoelectric effects in Z-type hexaferrites will enable this material to be applied in the novel low-power magnetoelectronic devices78.…”
mentioning
confidence: 95%
“…This allows device operation at both Global Positioning System (GPS) and Global Navigation Satellite System (GNSS) frequencies. This data shows promise for the development of miniature and high performance devices at UHF and L-band frequency [5,18]. Furthermore, due to the fact that wave impedance (Z) of the Co 2 Z is equivalent to that of air (Eqs.…”
Section: Orientation Effectmentioning
confidence: 97%
“…One promising method to achieve this goal is utilizing high permeability and permittivity materials with low magnetic losses [1][2][3][4][5][6]. However, most materials, such as cubic spinels and garnets, that exhibit high permeability values, also exhibit relatively low cutoff frequencies that prevent their use at higher rf and microwave frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, polycrystalline ferrite composites of nominal composition Ba 3 0.10, 0.15, and 0.20, were prepared by conventional ceramic processes. XRD studies revealed that the samples ranged from a nearly pure Z-type phase to composites with substantial Y type as a secondary phase.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Utilizing advanced materials processing technologies, high permeability and permittivity with low magnetic losses is a promising solution. As a critical component to radar and modern wireless communication systems, antenna elements with compact size are of highly valued.…”
mentioning
confidence: 99%